Psychoanalytic Reading of Desire for Freedom in Osamu Dazai’s The Setting Sun - Kevin Saputra; Zuhrul Anam (Universitas Negeri Semarang, 2025)
This study explores the psychological impact of Japan’s post-World War II defeat as depicted in Osamu Dazai’s The Setting Sun (1956), using Lacanian psychoanalysis to examine characters’ desires for freedom and identity reconstruction. Set against the collapse of traditional Japanese values and aristocracy, the novel reflects a society in transition from feudalism to industrial modernity. The research employs a descriptive qualitative method, focusing on close textual analysis to identify expressions of desire and internal conflict among the characters, particularly Kazuko and Naoji. Drawing on Lacan’s concepts of the Imaginary, the Symbolic, and the Real, the study investigates how language, social structures, and unconscious forces shape subjectivity. Data were categorized using an inventorying table, enabling thematic interpretation of the characters’ struggles with love, loss, autonomy, and societal expectation. Findings suggest that the characters’ fragmented identities mirror Japan’s cultural disorientation, highlighting how personal freedom becomes entangled with national trauma. This research offers insight into the ways literature can reflect and dramatize psychological crises, illustrating how postwar literature serves as both a cultural artifact and a means of exploring the human condition under historical rupture.